2014
DOI: 10.2478/s11756-014-0432-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silicon on maize seedlings exposed to short-term UV-B irradiation

Abstract: Enhanced UV-B irradiation is one of the most important abiotic stresses that can influence various aspects of plant morphology, biochemistry and physiology. Silicon as a beneficial element can increase the plant's tolerance against different abiotic stresses, including UV-B stress. In this work, the effect of silicon supplementation on the sensitivity of young maize (Zea mays L.) seedlings exposed to short-term UV-B radiation was studied. The seedlings were grown with 0 or 5 mM silicon in cultivation medium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Silicone can be applied to plants in many different forms. In the studies, it has been seen that silicon is applied in the forms of potassium silicate (28), silicon nanoparticles (18), sodium silicate (23), and silicic acid (20). Since silicon is taken from the soil by plants in the form of orthosilicic acid and is widely used in this form in in vitro studies, it is preferred in the form of orthosilicic acid for the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicone can be applied to plants in many different forms. In the studies, it has been seen that silicon is applied in the forms of potassium silicate (28), silicon nanoparticles (18), sodium silicate (23), and silicic acid (20). Since silicon is taken from the soil by plants in the form of orthosilicic acid and is widely used in this form in in vitro studies, it is preferred in the form of orthosilicic acid for the current study.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of UV-B and silicon on high silicon accumulators such as rice (29), corn (23), wheat (18), and soybean (20) were investigated, and A. thaliana, a model organism as a low silicon accumulator, has not been included in a recent study on UV-B and silicon together. Hence, A. thaliana was selected within the scope of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies regarding the addition of Si or Si nanoparticles have been reported for crop plants such as rice, wheat, and soybean ( Glycine max L.) ( Table 2 ). Such studies have shown that Si can reduce the negative effects of UV radiation through increased antioxidant capacity [ 3 , 4 ] and lower concentrations of ROS [ 5 ].…”
Section: Ultraviolet Radiationmentioning
confidence: 99%
“…Mihaličová Malčovská et al [ 5 ] exposed maize seedlings to short-term UV-B radiation. The seedlings were grown hydroponically and treated with Si or left untreated, as the control.…”
Section: Ultraviolet Radiationmentioning
confidence: 99%
See 1 more Smart Citation